Assessing Differences in Student Motivation, Achievement, and Conceptual Understanding in a Gamified Mathematics Learning Environment - Hassan Muhammad; Usman Garba; Nura AY Musa; Danladi Biong'ahu (Darul Yasin Al Sys, 2026)
Although gamified learning has received growing attention in mathematics education, empirical evidence on its simultaneous influence on students’ motivation, mathematics achievement, and conceptual understanding in developing educational contexts remains limited. This study examined differences in students’ motivation, mathematics achievement, and conceptual understanding associated with participation in a gamified mathematics learning environment. A quasi-experimental pretest–posttest control group design was employed, involving 700 secondary school students from 15 public schools in Northeast Nigeria. Using intact classes, students were assigned to an experimental group that received curriculum-aligned gamified mathematics instruction over a four-week period or to a control group that received conventional instruction covering the same content and duration. Data were collected using pretest and posttest measures of student motivation, mathematics achievement, and conceptual understanding. Motivation was assessed using an adapted questionnaire with established internal consistency, while achievement and conceptual understanding were measured using curriculum-aligned assessments validated through expert review. Data were analysed using descriptive statistics, paired-sample t-tests, and effect size estimates. The results showed statistically significant pretest–posttest gains in motivation, achievement, and conceptual understanding among students in the gamified instruction group, with moderate to large effect sizes, whereas students in the control group demonstrated minimal changes across the same measures. These findings indicate that curriculum-aligned gamified mathematics instruction is associated with enhanced student motivation, improved academic performance, and stronger conceptual understanding within the study context. The study contributes to mathematics education literature by providing large-sample quasi-experimental evidence on the concurrent affective and cognitive outcomes of gamified instruction in secondary mathematics classrooms in a developing educational setting.